Mudanças sutis na elevação determinam a estrutura das assembleias de morcegos Phyllostomidae na Amazônia central - Capaverde Junior, Ubirajara Dutra (Instituto Nacional de Pesquisas da Amazônia - INPA, 2015)
The spatial distribution of bat species has been linked to environmental factors resulting from landscape variation within ecosystems. However, within the same type of vegetation there are subtle differences that could potentially be associated with variations in bat assemblage composition. In the present study we evaluated the effect of food availability (fruits and insects), physical obstruction of vegetation and relief elevation in structuring phyllostomid bats assemblies in a flooded forest. The bats were captured using eight mist nets within 49 parcels over a 25 km2 section of the Ducke Reserve, central Brazilian Amazonia. In 7056 net- hours, 1138 individuals were captured belonging to 52 species. Elevation was the most important variable structuring species composition and abundance of bats assemblages. Suprisingly, the availability of plants with fruit was only the second most important variable in explaining assemblage composition in this group of frugivorous bats. Results indicated that, in general, composition of the understory of bat assemblage is related to local relief, however, for frugivorous species, food supply has greater influence on species distribution.
Keywords: Ecologia das comunidades; Altitude; Sub-bosque; Morcegos